2014
DOI: 10.1111/birt.12133
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of External Cephalic Version in the Netherlands: A Retrospective Cohort Study

Abstract: ECV implementation rates vary widely among hospitals. Suboptimal implementation is mostly caused by the care provider not offering the treatment and secondly due to women not opting for the offered attempt. A prerequisite for designing a proper implementation strategy is a detailed understanding of the exact reasons for not offering and not opting for ECV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 20 publications
1
22
1
2
Order By: Relevance
“…Much effort has been put into optimizing ECV success rates, including use of tocolytics . As a result of the reported safety , effectiveness , and cost‐effectiveness of ECV, ECV services are now in place in many units . Nevertheless, it is unclear how effective the implementation of ECV services has been as the incidence of breech presentation at term remains high and breech presentation remains a major contributor to both elective and emergency cesarean delivery rates .…”
mentioning
confidence: 99%
“…Much effort has been put into optimizing ECV success rates, including use of tocolytics . As a result of the reported safety , effectiveness , and cost‐effectiveness of ECV, ECV services are now in place in many units . Nevertheless, it is unclear how effective the implementation of ECV services has been as the incidence of breech presentation at term remains high and breech presentation remains a major contributor to both elective and emergency cesarean delivery rates .…”
mentioning
confidence: 99%
“…Indeed, this study showed that ET of ≤4 and ≤3 mm carried chances of having endometrial cancer of 1 in 282 and 1 in 383, respectively, which were much higher than the frequently quoted 1 in 917 chance (for ET of ≤ 4 mm) as reported by Goldstein in 2009. 2 In most institutions, including ours, 3 4-mm has been adopted as the cut-off and by changing that to 3-mm, an extra 20.8% of women will need ES, out of a total of 56.3%; but this will still miss 3.0% of endometrial cancer, which in this study can readily be picked up by ES.…”
mentioning
confidence: 82%
“…However, because a minimum of expertise in obstetric ultrasonography is necessary and experience may prove invaluable, each hospital should identify one or more health care practitioners who can develop and maintain the necessary expertise. Such set‐up is facilitated by the fact that ECV is generally a planned procedure and only fewer than 3 percent of women go into labor before the scheduled procedure . Concentrating scheduled ECV procedures to few enthused operators may provide the operators with greater chances to hone in their skills; however it is beneficial if all obstetricians have training to offer ECV to the woman who presents in early or prodromal labor with a previously undiagnosed breech.…”
Section: Methodsmentioning
confidence: 99%
“…As external cephalic version (ECV) has a success rate of about 50 percent , offering this procedure in cases of breech presentation at term is one of the ways to reduce the risk of cesarean delivery, with the associated risk of morbidity and mortality for women . Although most women with a successful ECV deliver vaginally , the procedure is underutilized: recent studies have shown that among cases of breech presentation at 36 weeks, an ECV was attempted in only 46 percent of them , and among breech deliveries at 40 hospitals in the Netherlands, ECV had not been attempted in 38 percent of cases without contraindications . The rate of implementation of ECV may vary widely within the same country (from 8 to 84% in the Netherlands) and the success of the procedure seems to be operator‐dependent .…”
mentioning
confidence: 99%